Pengaruh Split ‘V’ Stretch terhadap Kemampuan Servis Atas Double Event pada Atlet PSTI Kabupaten Demak (Universitas Negeri Semarang, 2021)
This study aims to determine the effect of the split 'v' stretch and split with the help of friends on the service results for the double event for PSTI athletes in Demak Regency in 2021. The method used was experimental with a population of 24 athletes and the sample used was all male sepaktakraw athletes in Demak Regency (total sampling). The test instrument uses Solomon's top service skill test instructions. The data analysis technique uses the SPSS25 calculation with the paired sample test method with the provisions of the Sig value. (2-tailed) < 0.05 then H0 is rejected and Ha is accepted (there is an effect). The results of the research hypothesis show; (1) The results of the calculation through spss with the paired sample test method are known to have an average (mean) pretest of -3250 this value shows the difference between the mean value of the experimental group 1 pretest and the posttest mean. Rated Sig. (2tailed) ie 1.764 > 0.05 (no effect). (2) The results of the calculation through spss with the paired sample test method are known to have an average (mean) pretest of -3000 this value shows the difference between the mean value of the experimental group 2 pretest and the posttest mean. Rated Sig. (2 tailed) that is 0.005 < 0.05 (no effect).